Lipid-rich carcinoma of the breast: A report of two cases and a literature review - CONG, YIZI (Oncol Lett, 2015)
Lipid-rich carcinoma of the breast is extremely rare with no standard guidelines for treatment with poor patient prognosis. In the present study, the clinical features, imaging results, pathology, immunohistochemistry, treatment and prognoses of two patients with lipid-rich carcinoma of the breast were analyzed. Two patients were admitted to the Yantai Yuhuangding Hospital Affiliated to the Medical College of Qingdao University (Yantai, Shandong, China) for examination of a palpable mass in the breast. Enlarged lymph nodes were found in the axilla of each patient. The results of mammography and echography imaging suggested the presence of malignancy. A modified radical mastectomy was performed in each patient, and pathological examination revealed atypical large vacuolated cells arranged in clusters and confirmed lipid-rich carcinoma and lymph node metastases. The tumor tissue of patient one was immunohistochemically positive for estrogen receptor (ER), p53, p120 and E-cadherin, and negative for progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER-2), with a Ki-67 labeling index of 50%. The tumor tissue of patient two was immunohistochemically positive for p53, and negative for ER, PR, HER-2 and cytokeratin 5/6, with a Ki-67 labeling index of 30%. Post-surgery, patient one was administered chemotherapy for six cycles, radiotherapy and endocrine therapy in the form of anastrozole. Patient two was administered three cycles of chemotherapy without radiotherapy. Subsequent to being followed up for 25 months and 13 months, respectively, there was no evidence of recurrence or distant metastasis in patient one or two, respectively.